Motor profile of students with dyslexia - Okuda, Paola Matiko Martins [UNESP] (2014)
In the presence of developmental dyslexia, there is high probability of motor difficulties being present as well purposes: The purposes of this study were to characterize and compare the motor performance of students with dyslexia with students with good academic performance and to identify the presence of the DCD (developmental coordination disorder) co-occurring with developmental dyslexia. A total of 79 students participated in the research, both genders, from 8 to 11 years old, from 3rd to 5th grades, and were divided into Group I: 19 students with developmental dyslexia and Group II: 60 students with good academic performance. All the students were assessed using “The Bruininks-Oseretsky Test of Motor Proficiency” (second edition), to measure the motor skills and the pattern and differences between groups. The results of this study showed that the motor performance of Group II students was superior to the performance of students of Group I in almost all motor areas assessed but both groups performed less well than they should have for their chronological age. The results of this study indicate that occupational therapists, speech therapists and educators need to be aware of the presence of motor impairments and the need for early intervention in both the academic and clinical environments, in order to ensure that early identification and diagnosis of possible co-occurrences, such as DCD, and the impact on learning to guarantee more appropriate clinical and educational assistance for this population. This may also indicate that increased exposure to movement may be important to limit some of the secondary health consequences in children in Brazil.